2007
DOI: 10.1051/agro:2007032
|View full text |Cite
|
Sign up to set email alerts
|

Replacing the nitrogen nutrition index by the chlorophyll meter to assess wheat N status

Abstract: absen

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
58
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 84 publications
(77 citation statements)
references
References 26 publications
13
58
0
Order By: Relevance
“…NNI was positively related to SPAD values. The increase in NNI with increasing N fertilization has been previously reported in corn (Plénet and Cruz, 1997;Ziadi et al, 2008) and in wheat (Debaeke et al, 2006;Prost and Jeuffroy, 2007). This positive relationship varied across different developmental stages and leaf positions.…”
Section: Correlation Of Spad and Rspad Values With Nni Atsupporting
confidence: 72%
See 1 more Smart Citation
“…NNI was positively related to SPAD values. The increase in NNI with increasing N fertilization has been previously reported in corn (Plénet and Cruz, 1997;Ziadi et al, 2008) and in wheat (Debaeke et al, 2006;Prost and Jeuffroy, 2007). This positive relationship varied across different developmental stages and leaf positions.…”
Section: Correlation Of Spad and Rspad Values With Nni Atsupporting
confidence: 72%
“…The non-linear relationship between SPAD values and NNI has been proved in fescue (Errecart et al, 2012), corn (Ziadi et al, 2008), wheat (Vouillot et al, 1998;Prost and Jeuffroy, 2007) and cocksfoot (Duru, 2002), and the correlation of RSPAD values with NNI, and relative grain yield has been studied only in corn (Ziadi et al, 2008) and wheat (Debaeke et al, 2006). Debaeke et al (2006) also found that the non-linear relationship between RSPAD values and NNI was not significantly affected by years, genotypes, and developmental stages.…”
mentioning
confidence: 99%
“…Adoption of this approach as a practical tool has been limited due to the substantial effort required in obtaining the plant samples. However, this approach is effective as a research tool, and has been used to develop critical petiole nitrate curves for potatoes (Be´langer et al 2003b) and to improve interpretation of SPAD-502 meter readings in wheat (Prost and Jeuffroy 2007).…”
Section: Plant-based Diagnostic Testsmentioning
confidence: 99%
“…The N status cannot be estimated from the leaf nitrogen content alone but biophysical parameters of the wheat canopy should also be taken into account. For example, the nitrogen nutrition index (NNI), i.e., the ratio between the actual N concentration (N t ) observed in the plants and the critical N concentration related to dry biomass (N ct ), has been used to reliably characterize the N status of wheat crops during the vegetative period [14]. NNI values >1 indicate excessive N supply (over-fertilization), whereas suboptimal N supply is indicated by values <1.…”
Section: Introductionmentioning
confidence: 99%